PENGEMBANGAN SELF-AWARENESS ANAK PANTI ASUHAN AISYIYAH PADANG MELALUI PELATIHAN REFLEKSI DAN KOMUNIKASI EMPATIK (Kolaborasi dengan Padang Sehat: Dukungan yang Tepat untuk Kesehatan Mental) - Yarisda, Viona Putri; Eriend, Dion; Flowerina, Indria; Edlina, Ria; Martha, Zike; Al Azizu, Khairannisa (Ensiklopedia Research and Community Service Review, 2025)
In accordance with the lecturers’ obligations in the Odd Semester of the 2024/2025 academic year as part of the Tri Dharma of Higher Education, one of the activities carried out was a Community Service Program entitled: “Self-Awareness: Becoming the Best Version of Yourself Through Self-Discovery” (a seminar held at Aisyiyah Orphanage, Padang). This activity served as both a responsibility in implementing the Tri Dharma and a social contribution from UNIDHA lecturers to the community. One important societal group that requires special attention is children in orphanages who are undergoing identity development. Many of them grow up in pressured environments and lack a proper understanding of themselves and the importance of mental health. Therefore, it is essential to provide early education on self-awareness and emotional regulation. The ability to recognize personal potential, understand emotions, and develop healthy interpersonal communication can help these children grow into more confident and resilient individuals. In this program, the UNIDHA team of lecturers provided training and guidance on self-reflection, mental strength, and empathic communication. Using methods such as lectures, interactive discussions, and simulations, participants were guided to formulate personal growth steps with a positive impact on themselves and their surroundings.Keywords: Self-awareness, Mental Health, Self-Reflection, Empathic Communication, Orphanage